Salicylate-induced Fanconi-like syndrome - Miltiadous, George; Tsimihodimos, Vasilis; Elisaf, Moses (Archives of Medical Science, 2009)
Salicylate intoxication is a very common problem in everyday clinical practice. We describe a new case of salicylate-induced reversible Fanconi\'s syndrome in a 28-year-old Cypriot male who ingested 50 g of acetylsalicylic acid with suicidal intent. To our knowledge, this is the second case ever described. It is suggested that clinicians should be aware of this salicylate intoxication-induced complication.